Impact of antenna array geometry on the capacity of mimo communication system - Hassan, Muhammad Tanvir; Morshed, S. M. Nurul; Mahbub-Ul-Alam (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.